2017
DOI: 10.3390/molecules22040589
|View full text |Cite
|
Sign up to set email alerts
|

ABC Transport Proteins in Cardiovascular Disease—A Brief Summary

Abstract: Adenosine triphosphate (ATP)-binding cassette (ABC) transporters may play an important role in the pathogenesis of atherosclerotic vascular diseases due to their involvement in cholesterol homeostasis, blood pressure regulation, endothelial function, vascular inflammation, as well as platelet production and aggregation. In this regard, ABC transporters, such as ABCA1, ABCG5 and ABCG8, were initially found to be responsible for genetically-inherited syndromes like Tangier diseases and sitosterolemia. These find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 128 publications
(150 reference statements)
0
69
0
6
Order By: Relevance
“…Both genes ABCG5 and ABCG8 are located head to head on chromosome 2p21, and each gene encodes a “half‐ATP binding cassette transporter” that is nonfunctional in the monomeric state and that pump sterols out to intestinal lumen or into bile . However, assembly of an ABCG5/G8 heterodimer, driven by the adipocyte‐derived hormone leptin, leads to the formation of the fully‐functional transporter ABCG5/G8 . It has been demonstrated that ABCG5/G8 is exclusively expressed on the apical membranes of enterocytes and hepatocytes .…”
Section: Molecular Defects Of Hereditary Stomatocytosismentioning
confidence: 77%
See 1 more Smart Citation
“…Both genes ABCG5 and ABCG8 are located head to head on chromosome 2p21, and each gene encodes a “half‐ATP binding cassette transporter” that is nonfunctional in the monomeric state and that pump sterols out to intestinal lumen or into bile . However, assembly of an ABCG5/G8 heterodimer, driven by the adipocyte‐derived hormone leptin, leads to the formation of the fully‐functional transporter ABCG5/G8 . It has been demonstrated that ABCG5/G8 is exclusively expressed on the apical membranes of enterocytes and hepatocytes .…”
Section: Molecular Defects Of Hereditary Stomatocytosismentioning
confidence: 77%
“…It has been demonstrated that ABCG5/G8 is exclusively expressed on the apical membranes of enterocytes and hepatocytes . The heterodimer is responsible for the efflux of cholesterol and plant sterols either by hepatocytes into the bile or through the enterocytes of the intestine back into the intestinal lumen for fecal disposal …”
Section: Molecular Defects Of Hereditary Stomatocytosismentioning
confidence: 99%
“…ABCA1 can prevent foam cell formation by exporting excessive cholesterol from lipid-loaded macrophages and maintain cellular lipid and cholesterol homeostasis [33]. Firstly, we examined the effects of apigenin on macrophage ABCA1 expression and ABCA1-mediated cholesterol efflux.…”
Section: Apigenin Stimulates Abca1 Expression and Abca1-mediated Cholmentioning
confidence: 99%
“…GLUT2 movement to the apical membrane may be concerted with insulin signaling. Therefore, insulin resistance in T2DM would lead to increased and less regulated GLUT2 translocation to the apical membrane and glucose absorption, causing higher hyperglycemia in T2DM cases [13,18]. There exists a correlation between fructose consumption through food and T2DM occurrence, and fructose transporter GLUT5 may also play a role in the development of T2DM.…”
Section: Glucose Transporter/slc2 (Glut) Familymentioning
confidence: 99%